Pengaruh Pembelajaran Technopreneurship Berbasis Project Based Learning dan Sikap Kewirausahaan Terhadap Minat Berwirausaha Peserta Didik - Nabilla Umami; Dewi, Retno Mustika (International Journal Administration, Business & Organization, 2025)
Entrepreneurship is one of the activities that has the potential to minimize unemployment rates while optimizing economic productivity in a country. However, the reality shows that students are not too interested in entrepreneurial activities. In an effort to foster students' entrepreneurial spirit, external and internal factors are needed that influence students' interest in entrepreneurship, including through technopreneurship learning and entrepreneurial attitudes. The purpose of this study is to determine the effect of technopreneurship learning and entrepreneurial attitudes on students' interest in entrepreneurship. The associative causal research method with a quantitative approach was applied in this study, by applying multiple linear regression analysis techniques assisted by IBM SPSS version 25 software. The sample used in this study was 36 students of SMA Semen Gresik in grades X to XII who had participated in the technopreneurship learning program. This study found that technopreneurship learning and entrepreneurial attitudes possessed by students simultaneously influenced students' interest in entrepreneurship. Meanwhile, it was partially found that technopreneurship learning did not have a significant effect on students' interest in entrepreneurship, while entrepreneurial attitudes had a significant effect on interest in entrepreneurship. With the findings of this study, it is hoped that schools will always help maximize the learning process of students, especially in studying entrepreneurship, so that students' interest in entrepreneurship increases.